Lost in translation: true clinical impact of reflectance confocal microscopy overlooked in 'Biopsy outperforms reflectance confocal microscopy in diagnosing and subtyping basal cell carcinoma: results and experiences from a randomized controlled multicentre trial'. (1st April 2021) - Gill, M.; Pellacani, G.; Grant‐Kels, J.M.; Ardigò, M.; Chen, C.‐S.J.; Gonzalez, S.; Guitera, P.; Longo, C.; Malvehy, J.; Markowitz, O.; Puig, S.; Rabinovitz, H.; et al.
Abstract: Linked Article:  Woliner‐van der Weg et al . Br J Dermatol 2021; 184 :663–671 .